Resistance-related physiological response of rice leaves to the compound stress of enhanced UV-B radiation and Magnaporthe oryzae. Issue 1 (1st January 2018) - He, Yongmei; Li, Xiang; Zhan, Fangdong; Xie, Chunmei; Zu, Yanqun; Li, Yuan; Yue, Ming
ABSTRACT: An enhanced UV-B radiation (5.0 kJ m −2 ) was supplied before, during, and after Magnaporthe oryzae infection. The effects of single and compound stress of the UV-B radiation and M. oryzae on the resistance physiology and gene expression of rice leaves were examined. Results revealed that UV-B radiation given before M. oryzae infection (UV-B → M.) significantly increased the pathogenesis-related proteins (PRs) activities of phenylalanine ammonialyase (PAL), lipoxygenase (LOX), chitinase (CHT), and β-1, 3-glucanase, the resistance-related substances (flavonoids and total phenols) content, and resistance-related genes (OsPAL and OsCHT) expression, thereby improving the disease resistance of rice leaves. Simultaneous exposure to UV-B radiation and M. oryzae (UV-B/M.) significantly increased the OsLOX2 expression and the PRs activities. Exposure to UV-B radiation after M. oryzae infection (M. → UV-B) decreased the flavonoid content, did not improve the PRs activity, and increased OsLOX2 expression. Compound treatments of UV-B → M., UV-B/M., and M. → UV-B reduced the disease index by 62.3%, 40.2%, and 26.6%, respectively, indicating UV-B radiation inhibited the occurrence of M. oryzae disease, but its inhibitory effect weakened when it was provided after M. oryzae infection. Hence, rice responded to the compound stress of UV-B radiation and M. oryzae through a resistance-related physiological mechanism associated with the sequence of stress occurrence.